DISPOSABLE SURGICAL FACE MASKS: A SYSTEMATIC REVIEW - Lypp, Allyson; Edwards, Peggy (Operating Room Nurses Association of Canada Journal, 2005)
Surgical face masks were originally developed to contain and filter droplets of microorganisms expelled from the mouth and nasopharynx of healthcare workers during surgery, thereby providing protection for the patient. However, there are several ways in which surgical face masks could potentially contribute to contamination of the surgical wound. Surgical face masks have recently been advocated as a protective barrier between the surgical team and the patient, but the role of the surgical face mask as an effective measure in preventing surgical wound infections is questionable.